Development of an improved geomagnetic reference field of Antarctica - De Santis, A.; Chiappini, M.; Torta, J. M.; von Frese, R. R. B. (Annals of Geophysics, 1999)
The properties of the Earth's core magnetic field and its secular variation are poorly known for the Antarctic. The increasing availability of magnetic observations from airborne and satellite surveys, as well as the existence of several magnetic observatories and repeat stations in this region, offer the promise of greatly improving our understanding of the Antarctic core field. We investigate the possible development of a Laplacian reference model of the core field from these observations using spherical cap harmonic analysis. Possible uses and advantages of this approach relative to the implementations of the standard global reference field are also considered.